We'll use the formula of the derivative of a quotient: `(u/v)' = (u'v-u v')/v^2.` Here u=`ln(t)` and `v=t,` therefore `u'=1/t` and `v'=1.` So

`h'(t) = (1/t *t - ln(t))/t^2 = (1 - ln(t))/t^2.`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now